Analysis Use Artistic in Television Program Production Hells Kitchen Indonesia to Meaning Symbols Presented​ - Hakima, Muhammad Fardan; Nafsika, Salsa Solli; Undiana, Nala Nandana (Jurnal Abdimas, 2024)
The television media industry in Indonesia has diversity pattern broadcasting and the target market. As for television program entertainment facilities must own diverse the method used to make the program created Can accepted and enjoyed by many market circles. But in reality the mass media industry which includes inside it television convey message, feeling or meaning other Can expressed with A appearance artistic in the program. The purpose of the analysis This For dissect more in meanings – meanings artistic What only what is in it A impressions television through theories put forward by experts semiotics famous namely John Fiske. In the analysis carried out with base observation from television programs owned by SCTV entitled Hell's Kitchen Indonesia, a reality competition show wrapped cooking​ with the reality that occurs in the kitchen restaurant in fact. It was found that A reality condition chef's kitchen that can wrapped up meanings - meanings implied through side artistic sign costume, interior, exterior, technical camera and elements​​ the color displayed. Symbol the can give strength in convey A message certain.